Small bowel protection in IMRT for rectal cancer: a dosimetric study on supine vs. prone position - Köck, Julia; Kromer, Katharina; Siebenlist, Kerstin; Mai, Sabine; Büttner, Sylvia; Fleckenstein, Jens; Wenz, Frederik (Strahlentherapie und Onkologie, 2017)
Background: This treatment planning study analyzes dose coverage and dose to organs at risk (OAR) in intensity-modulated radiotherapy (IMRT) of rectal cancer and compares prone vs. supine positioning as well as the effect of dose optimization for the small bowel (SB) by additional dose constraints in the inverse planning process. Patients and methods: Based on the CT datasets of ten male patients in both prone and supine position, a total of four different IMRT plans were created for each patient. OAR were defined as the SB, bladder, and femoral heads. In half of the plans, two additional SB cost functions were used in the inverse planning process. Results: There was a statistically significant dose reduction for the SB in prone position of up to 41% in the high and intermediate dose region, compared with the supine position. Furthermore, the femoral heads showed a significant dose reduction in prone position in the low dose region. Regarding the additional active SB constraints, the dose in the high dose region of the SB was significantly reduced by up to 14% with the additional cost functions. There were no significant differences in the dose distribution of the planning target volume (PTV) and the bladder. Conclusion: Prone positioning can significantly reduce dose to the SB in IMRT for rectal cancer and therefore should not only be used in 3D conformal radiotherapy but also in IMRT of rectal cancer. Further protection of the SB can be achieved by additional dose constraints in inverse planning without jeopardizing the homogeneity of the PTV.